The DINARC© Toolkit - Clinical Academic Research Capacity-Building and Post-Doctoral Development for Nurses, Midwives and Allied Health Professionals (NMAHP) - Iles-Smith, Heather; Ersser, Steven (International Journal of Practice-based Learning in Health and Social Care, 2019)
The challenges of developing nurses, midwives and AHPs (NMAHPs) as clinical academics (CA) have received international attention. Balancing clinical practice and academic pursuit, often where managers are unfamiliar with academic career requirements, is one such challenge; however, the current literature provides limited developmental guidance. The aim of this article is to describe the DINARC© (Dissemination, Implementation, Networking, Active Research and Clinical practice) Toolkit, a continuous practice development aide for NMAHPs who are in the early post-doctoral phase of a clinical academic career (CAC). We identified five DINARC© elements, through evidence review and synthesis, as requisites for supporting the progression of a CAC. An ‘expert reference group’ (CAs, academic supervisors and nurse leaders) advised and assisted in development of the DINARC© concept. A Practitioner Research Plan and Mentor–Mentee Discussion Guide was developed and applied within a large metropolitan UK university teaching hospital; this was designed to identify the essential elements required to successfully navigate a CAC pathway. Early feedback from practitioners and managers suggests that DINARC© aids CAs in navigating an early CAC and offers guidance for managers. Further application and evaluation of DINARC© is now required by those developing a CAC. Implications for practice: DINARC© is a resource to guide practitioners’ CAC development with the goal of integrating and strengthening clinically-based NMAHP research activities, with related improvements in patient care. We believe that DINARC© has wider relevance as a useful tool, worthy of testing internationally.